Fatigue and symptoms of eating disorders in professional dancers Fadiga e sintomas de transtornos alimentares em bailarinos profissionais - Rodrigues Y.C.F.* (2017)
© 2017, Universidade Federal de Santa Catarina. All rights reserved.The aim of this study was to make a comparison between fatigue and eating disorders in professional dancers in Brazil. Overall, 108 Classical Ballet or Contemporary Dance dancers (28.6 ± 7.7 years) (49 women and 59 men) of companies from São Paulo, Rio de Janeiro, Minas Gerais and Rio Grande do Sul participated in this study. The following validated instruments were used (Eating Attitudes Test; Bulimic Inventory Test Edinburgh; Yoshitake Fatigue Questionnaire, general Information). Results: 16% of dancers have symptoms of anorexia; 25% in the symptomatic bulimia scale and 30% in the bulimia scale. Significant data were identified in the comparison of bulimia nervosa scales with fatigue domains; on the symptomatic scale with drowsiness and lack of attention at work domain (p = 0.015), on the severity scale with fatigue projections to the body domain (p = 0.014), and in both scales in the impaired concentration and attention domain (p = 0.003 and p = 0.047) and in the general fatigue score (p = 0.016). Dancers with higher scores for difficulty in concentration and attention are 1.558 (95% CI 1.113 to 2.179) times more likely to have symptoms of bulimia. This study showed that there is a relationship between fatigue and symptoms of bulimia.